Answer : The statement is false for any value of because the even root function is always positive or
Answer:
86°
Step-by-step explanation:
124 + 40 + 110 = 274
360 - 274 = 86°
x2=36
We move all terms to the left:
x2-(36)=0
We add all the numbers together, and all the variables
x^2-36=0
a = 1; b = 0; c = -36;
Δ = b2-4ac
Δ = 02-4·1·(-36)
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
x1=−b−Δ√2ax2=−b+Δ√2a
Δ‾‾√=144‾‾‾‾√=12
x1=−b−Δ√2a=−(0)−122∗1=−122=−6
x2=−b+Δ√2a=−(0)+122∗1=122=6
Answer:
3(4x - 1)(2x + 3)
Step-by-step explanation:
Rearrange the equation into standard form
Subtract 9 - 30x from both sides
24x² + 30x - 9 = 0 ← in standard form
Take out 3 as a common factor
3(8x² + 10x - 3) = 0 ← factor the quadratic
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x term
product = 8 × - 3 = - 24, sum = 10
The factors are - 2 and + 12
Use these factors to replace the x- term, that is
8x² - 2x + 12x - 3 ( factor the first/second and third/fourth terms )
2x(4x - 1) + 3(4x - 1) ← take out the common factor (4x - 1)
(4x - 1)(2x + 3)
24x² + 30x - 9 = 3(4x - 1)(2x + 3) ← in factored form
When multiplying numbers with exponents, add the exponents.
So the answer is 2^-16